Outcomes of repeat kidney transplantation following prior graft failure secondary to BK nephropathy: A single‐center retrospective study. Issue 4 (9th July 2021) - Dong, Rachel; Shetty, Aneesha; Tambur, Anat R; Ison, Michael G.
Abstract: Background: BK virus is associated with development of nephropathy (BKVN) that can lead to graft failure after renal transplantation. There are limited data on rates of recurrence and outcomes of repeat renal transplantation after prior graft loss caused by BKVN. Methods: After IRB approval, data on all patients who underwent a repeat renal transplantation after prior graft failure as a result of BKVN were identified. Data on management of patients prior to retransplantation, induction and maintenance immunosuppression, and key clinical and virologic outcomes were collected. Descriptive statistics were used for analysis. Results: Thirteen patients were identified over a 13‐year period, and follow‐up of these patients occurred for a median of 4.7 years. Most patients have previous renal transplants removed prior to (7/13, 53.8%) or at the time of retransplantation (3/13, 23.1%). Close virologic monitoring of serum and urine, coupled with early immunosuppression minimization, was associated with few patients developing BK viruria above 1 × 10 7 c/mL (4/13, 30.8%), BK viremia above 10, 000 c/mL (2/13, 15.4%), and biopsy‐proven BKVN (1/12, 8.3%); most (8/13, 61.5%) developed BK viruria at any level. Renal function at 1 year post‐retransplantation was generally excellent and only 1 patient developed graft failure caused by recurrent focal segmental glomerulosclerosis. In our review of the literature, 2 large observational studies of the UNOS database as well as our analysis of case reports showed excellent graft survival and very low rates of recurrent BKVN leading to graft loss. Conclusions: Retransplantation after prior graft failure caused by BKVN generally has low rates of recurrence when coupled with close monitoring and early immunosuppression minimization. Removal of failed renal transplant may allow easier monitoring for recurrence.